“An Emergency Within the Emergency”: The Effect of Government Policies on the Mental Health and Wellbeing of the Population of England During the Covid-19 Pandemic - Susan Barrett (Revue Française de Civilisation Britannique)
During the Covid-19 pandemic, the lockdown and containment measures that were put in place by the UK government severely disrupted NHS mental health services. Surveys carried out during this period showed a decline in people’s wellbeing leading to fears that the country would soon face an unprecedented mental health crisis. This paper shows that not everyone was affected in the same way and that those whose mental health deteriorated the most were those who had already been most at risk prior to the pandemic. It concludes that rather than creating a new crisis, the pandemic merely exacerbated existing problems.